Effect of biofuels on composite propellant workflow diesel - Кухарёнок, Г.М.; Бармин, В.А. (Proceedings of National Aviation University, 2009)
Results of mathematical modelling of working process of a diesel engine with the account fiziko - chemical properties of a mix of diesel fuel with a methyl aether raps oils. Are resulted influence of a mix of biofuel on ecological and dynamic indicators about process of combustion, characteristics of burning out of fuel and display indicators of a cycle is defined.